2017
DOI: 10.1016/j.foodhyd.2017.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of cereal β-glucan at low concentrations

Abstract: Viscosity of cereal β-glucan during digestion is considered to be a vital factor for its health effects. Thus, studies on solution properties and gelation are essential for understanding the mechanisms of the β-glucan functionality. The aim of this study was to investigate the effect of the dissolution temperature on gelation of cereal β-glucan at low concentrations that are relevant for food products. The rheological properties of oat and barley β-glucans (OBG and BBG) using three dissolution temperatures (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In other studies, it was observed that the high concentration of β-glucan molecules affected their greater affinity to each other, which led to the formation of a hydrogel (Kurek et al., 2017b). The lack of high differences in the nominal values of the observed parameters between oat flours and barley flours can be explained by the fact that the gel-forming links are not only formed by cellotriose units, but also by undissolved β-glucan fractions (Mäkelä et al., 2017). Moreover, each β-glucan containing raw material was added in the same amount but with different concentrations of β-glucan.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, it was observed that the high concentration of β-glucan molecules affected their greater affinity to each other, which led to the formation of a hydrogel (Kurek et al., 2017b). The lack of high differences in the nominal values of the observed parameters between oat flours and barley flours can be explained by the fact that the gel-forming links are not only formed by cellotriose units, but also by undissolved β-glucan fractions (Mäkelä et al., 2017). Moreover, each β-glucan containing raw material was added in the same amount but with different concentrations of β-glucan.…”
Section: Resultsmentioning
confidence: 99%
“…This complex flow behavior is often observed for gelled suspensions 27 and is also reported for other concentrated glucan dispersions. 21,22 The reversibility of the flow curve shown in Figure 6a shows that, for a dispersion derived from the pre-dispersed 9.3 wt % industrially pressure homogenized sample of α-1,3-glucan, any additional shearing during rheological measurement does not result in any change in rheological properties. However, the additional dispersion method itself significantly affects the flow curve, as shown in Figure 6b.…”
Section: Additional Processingmentioning
confidence: 98%
“…For example, the thermal treatment and processing history, such as mixing and dispersion procedures, are known to affect the technological functionality of many polysaccharides, including β-glucans. 21 The dispersion characteristics 22 and rheology 23 found in the literature for β-glucans provide a useful framework for studies of new glucan systems.…”
Section: Introductionmentioning
confidence: 99%
“…We selected thermal treatment, UT, and combination of UT with MF (UT+MF). The first method is commonly employed for solubilization of β-glucan (Mäkelä et al 2017), while UT and UT+MF were selected to understand possible changes induced to IOF. UT and MF are among the most commonly used methods for emulsion preparation, thus, were employed here to prepare IOF-stabilized emulsions (McClements 2016).…”
Section: Behavior and Physical Stability Of Oat Fractions In Different Media And Under Different Treatmentsmentioning
confidence: 99%